Improved Decoy-State Measurement-Device-Independent Quantum Key Distribution With Imperfect Source Encoding - Xingyu Zhou; Chunmei Zhang; Guangcan Guo; Qin Wang (IEEE Photonics Journal, 2019)
Measurement-device-independent quantum key distribution (MDI-QKD) is designed to be secure against any detector-side channel attacks. However, assumption of characterized sources in preparation is a demanding requirement and can not be fully satisfied in real-life implementations. Luckily, by utilizing the data of mismatched bases, the system can even generate secure keys with uncharacterized sources. Here, we give a framework on investigating the practical performance of an improved MDI-QKD with uncharacterized sources, where the three-intensity decoy-state method is employed and full parameter optimizations are applied. Simulation results show that the improved method can significantly enhance the performance compared with the original MDI-QKD with uncharacterized sources.